HUBUNGAN ANTARA DUKUNGAN TEMAN SEBAYA DAN SELF-COMPASSION TERHADAP SELF-ESTEEM DI SEKOLAH MENENGAH PERTAMA - Rifai, Nabila Rana; Muslikah (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study focuses on the relationship between peer support and self-compassion on self-esteem possessed by junior high school students. This article aims to explore the important role of self-esteem in the development of early adolescence (junior high school). The peer support scale is (Solomon, 29 items), self-compassion scale (Neff & Germer, 37 items), and self-esteem scale (Rosenberg, 29 items). This study uses a quantitative correlational approach with data collection techniques using interviews, questionnaires and psychological scales in the form of a Likert scale. The population is 676 and the number of samples is 251 junior high school students in Plered District, Cirebon using random sampling and using the slovin technique. The results of the validity and reliability tests on the peer support instrument (0.925), self-compassion (0.958), and self-esteem (0.938) are declared valid and reliable. Data analysis used in this study was by using multiple linear regression analysis. The results showed that peer support, self-compassion and self-esteem in students at SMPN Se-Kecamatan Plered Cirebon were in the High category. There was a relationship of 43.2% between peer support and self-compassion on students' self-esteem. The remaining percentage was influenced by other variables not examined in this study. The researcher recommends that guidance and counseling (BK) teachers be able to design individual and group counseling service programs, classical services. Meanwhile, for further researchers, it is recommended to expand the scope of research subjects, and add other variables that may affect self-esteem.